Echovirus Infection and Basal Ganglia Edema - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The case of a 4-year-old girl with bilateral edema of the basal ganglia in association with echo type 21 viral infection is reported from the University Hospitals of Munster and Hamburg, Germany.